Analysis and Effects on the Merging of International Financial Reporting Ethics in the Indian Corporate Sector - Surajit Singha (Management Journal for Advanced Research, 2023)
In the current era of globalisation, more than 3600 multinational corporations are establishing operations in India's various industries. These Indian corporations are disclosing their financial information in accordance with IFRS, Indian GAAPs, US GAAPs, Japan GAAPs, etc. In an effort to avoid this kind of trouble, the accounting bodies around the world are striving towards a uniform set of accounting policies, valuation standards, and disclosure criteria. In this circumstance, India must move from Indian GAAP to IFRS across all industries. India, a rising nation on the global economic map, also made the decision to converge with IFRS by creating a standard known as Ind AS. The current paper's objectives are to ascertain the level of stakeholder awareness regarding the adoption of IFRS in India and the effects of IFRS convergence on various industries. The researcher discovered that there are several ways to grasp IFRS, and the results indicate that there is a significant need for training and knowledge in this area as well as a lot of support from various sectors for the adoption process.